2007
DOI: 10.1136/tc.2006.019794
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost effectiveness of telephone counselling and the nicotine patch in a state tobacco quitline

Abstract: Objectives: State and national tobacco quitlines have expanded rapidly and offer a range of services. We examined the effectiveness and cost effectiveness of offering callers single session versus multisession counselling, with or without free nicotine patches. Methods: This 362 randomised trial included 4614 Oregon tobacco quitline callers and compared brief (one 15-minute call), moderate (one 30-minute call and a follow-up call) and intensive (five proactive calls) intervention protocols, with or without off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 51 publications
14
169
2
5
Order By: Relevance
“…All counselors were bachelors or masters-level providers with at least 3 years of general counseling experience, consistent with prior QL (Hollis et al, 2007;Stead et al, 2013) and ACT intervention trials (Dahl, Wilson, & Nilsson, 2004;Forman et al, 2007;Lappalainen et al, 2007). Counselors completed at least 100 hr of training in the treatment approach that they delivered and, prior to beginning as a study counselor, demonstrated acceptable adherence to the intervention protocol using standardized rating procedures.…”
Section: Counselor Qualifications and Trainingmentioning
confidence: 97%
See 4 more Smart Citations
“…All counselors were bachelors or masters-level providers with at least 3 years of general counseling experience, consistent with prior QL (Hollis et al, 2007;Stead et al, 2013) and ACT intervention trials (Dahl, Wilson, & Nilsson, 2004;Forman et al, 2007;Lappalainen et al, 2007). Counselors completed at least 100 hr of training in the treatment approach that they delivered and, prior to beginning as a study counselor, demonstrated acceptable adherence to the intervention protocol using standardized rating procedures.…”
Section: Counselor Qualifications and Trainingmentioning
confidence: 97%
“…The estimate of the number of calls completed was 3.5 (SD = 1.3) for ACT (Bricker et al, 2010) and 2.3 (SD = 1.6) for CBT (Hollis et al, 2007). Based on these estimates, there was 80% power to detect a significant difference in number of completed calls (60 per arm).…”
Section: Sample Sizementioning
confidence: 97%
See 3 more Smart Citations